Mode Selection for Device-To-Device Communication Underlaying an LTE-Advanced Network - Doppler, Klaus; Chia-Hao Yu; Ribeiro, Cássio B; Jänis, Pekka (2010 IEEE Wireless Communication and Networking Conference, 2010)
Device-to-Device communication underlaying a cellular network enables local services with limited interference to the cellular network. In this paper we study the optimal selection of possible resource sharing modes with the cellular network in a single cell. Based on the learning from the single cell studies we propose a mode selection procedure for a multi-cell environment. Our evaluation results of the proposed procedure show that it enables a much more reliable device-to-device communication with limited interference to the cellular network compared to simpler mode selection procedures. A well performing and practical mode selection is critical to enable the adoption of underlay device-to-device communication in cellular networks.